The need for and provision of intrathecal baclofen therapy for the management of spasticity in England: an assessment of the Hospital Episode Statistics database. Issue 6 (30th June 2015) - Narendran, Rajesh C; Duarte, Rui V; Valyi, Andrea; Eldabe, Sam
Abstract : Objectives: The aim of this study was to evaluate changes in the uptake of intrathecal baclofen (ITB) following commissioning of this therapy by the National Health Service (NHS) England in April 2013. The specific objectives of this study were: (i) to explore the gap between the need for and the actual provision of ITB services; and (ii) to compare England figures with other European countries with comparable data available. Setting: Data for ITB -related procedures were obtained from the Hospital Episode Statistics (HES) database from 2009/2010 to 2013/2014. Participants: Patients receiving ITB for the management of spasticity. Results: The available data for implantation of ITB from 2009/2010 to 2013/2014 for the treatment of spasticity due to varied aetiologies show that there has not been an increase in uptake of this therapy. The estimated need for this treatment based on the incidence and prevalence of conditions susceptible to ITB therapy is between 4.6 and 5.7 per million population. Our analysis of the data available from the HES database showed that the actual number of implants is around 3.0 per million population. The same period 2009–2014 has seen an increase in the delivery of other neuromodulation techniques including spinal cord stimulation, deep brain stimulation and sacral nerve stimulation. Conclusions: There is a considerable gap between the need for and provision of ITB figures nationally. Additionally, within the same area, we have observed important differences in the ITB service delivery between the various trusts. The reasons for this can be multifactorial, including individual experience and opinions, organisational structures, resource and financial limitations. Further research analysing the efficacy and cost-effectiveness of this treatment in the UK might inform the development of Technology Appraisal Guidance for ITB, potentially leading to an improvement in service provision.